WORKPLACE EMPOWERMENT AND JOB SATISFACTION IN PORTUGUESE NURSING STAFF: AN EXPLORATORY STUDY - Maria Helena de Almeida; Alejandro Orgambídez-Ramos; Paula Batista (University of Ostrava, 2017)
Aim: The aim was to examine to what extent structural empowerment (access to opportunities, support, information, and resources), and global empowerment predict job satisfaction in a sample of nursing staff from the south of Portugal. Design: A cross-sectional correlational study was made. Methods: Of 205 professional nursing surveyed, a final sample of 151 participants was selected from two public hospitals. To measure structural and global empowerment and work satisfaction, Portuguese versions of the Conditions for Work Effectiveness Questionnaire (CWEQ-II) and Job Satisfaction Scale were used. We used STATA software and an alpha level of 0.05 for all statistical levels to analyse the common variance method (CMV), correlations, and hierarchical multiple regressions. Results: All dimensions of structural empowerment (access to opportunities, information, resources, and support) and global empowerment were positively and significantly (level of significance 95%) related to job satisfaction. Regression models showed that job satisfaction was significantly predicted by access to opportunities and global empowerment. Conclusion: Working conditions characterized by empowerment and opportunities for growth and development are important determinants of job satisfaction among nurses. Managers should make an effort to provide opportunities to learn and put into practice new knowledge and skills in the workplace, increasing empowerment levels and job satisfaction in nursing staff. Keywords: global empowerment, nurses, predict, structural empowerment, work satisfaction.